Hygiene Sanitation and Rhodamin B Dyes in Cenil: Study in Sub-District Market of Jember District - Charisma Try Ristianingrum; Anita Dewi Moelyaningrum; Rahayu Sri Pujiati (State Islamic University of Sunan Ampel, 2018)
Cenil is still one of the traditional foods that people are interested in nowadays. To make it look attractive, cenil producers often use red coloring substance such as Rhodamine B. Rhodamin B is one type of textile dye that is prohibited from being used in food. Many cases of food poisoning or illness are caused by insecure food consumed, lack of application of hygiene sanitation and the use of hazardous chemical dyes as additional ingredients in Cenil. This research used descriptively with quantitative approach. The population of the study was the producer of the cenil as many as seven producers that are selling at the spread in 4 traditional markets in 3 sub-district of Jember District. The sample in this study is total population. The result of the knowledge level of cenil respondents related to the use of additives dye has a medium category (57%). The result hygiene sanitation of cenil has a good selection quality (57%). The result of a laboratory test to the existence of Rhodamin B dye on cenil showed two samples (29%) which contain positive Rhodamin B. Identification the difference of cenil which containing Rhodamine B have bright pink color, tend to fluoresce, there are nonhomogeneous color spots and bitter taste.